(untitled) (African Journal of Law and Politics, 2023)
Cameroon Penal Code that was thoroughly review in July 12, 2016 has nevertheless maintained untouched as main penalty, the capital punishment likely to be inflicted on criminal offenders. Apart from this legal instrument, three other laws enshrine the death penalty in Cameroon. There are respectively the law against terrorism of December 23, 2014, the law regulating the use of force and ammunitions of December 14, 2016 and the law laying down the Code of Military Justice of July 12, 2017. However, as long as the State of Cameroon will not follow the footsteps of abolitionist countries, it becomes obvious that a lot must be done for offenders liable to death penalty to have access to quality defense. Unfortunately, going by observation of defense strategies adopted by lawyers in courthouses, it is clear that a long way is still to go. This work seeks to serve as a legal and strategic underpinning to lawyers in matters where their clients are likely to incur the death penalty. A good mastery of international instrument in capital punishment and the reliance on diagnostic inquiries that spelt out the past of the presumed offender are indispensable prerequisites in carrying out a defense that might result in sparing the accused from a merciless punishment.